Why electricity market models yield different results: Carbon pricing in a model-comparison experiment - Oliver Ruhnau; Michael Bucksteeg; David Ritter; Richard Schmitz; Diana Böttger; Matthias Koch; Arne Pöstges; Michael Wiedmann; Lion Hirth (ZBW - Leibniz Information Centre for Economics, 2021)
The European electricity industry, the dominant sector of the world's largest cap-and-trade scheme, is one of the most-studied examples of carbon pricing. In particular, numerical models are often used to study the uncertain future development of carbon prices and emissions. While parameter uncertainty is often addressed through sensitivity analyses, the potential uncertainty of the models themselves remains unclear from existing single-model studies. Here, we investigate such model-related uncertainty by running a structured model comparison experiment, in which we exposed five numerical power sector models to aligned input parameters—finding stark model differences. At a carbon price of 27 EUR/t in 2030, the models estimate that European power sector emissions will decrease by 36–57% when compared to 2016. Most of this variation can be explained by the extent to which models consider the market-driven decommissioning of coal- and lignite-fired power plants. Higher carbon prices of 57 and 87 EUR/t yield a stronger decrease in carbon emissions, by 45–75% and 52–80%, respectively. The lower end of these ranges can be attributed to the short-term fuel switch captured by dispatch-only models. The higher reductions correspond to models that additionally consider market-based investment in renewables. By further studying cross-model variation in the remaining emissions at high carbon prices, we identify the representation of combined heat and power as another crucial driver of differences across model results.
Additional information: Please cite as: Ruhnau, Oliver, Michael Bucksteeg, David Ritter, Richard Schmitz, Diana Böttger, Matthias Koch, Arne Pöstges, Michael Wiedmann & Lion Hirth (2022): “Why electricity market models yield different results: Carbon pricing in a model-comparison experiment”, Renewable and Sustainable Energy Reviews, https://doi.org/10.1016/j.rser.2021.111701; More recent version: https://doi.org/10.1016/j.rser.2021.111701
Keywords: Q4; Q5; 330; Carbon pricing; EU Emission Trading System (EU ETS); Electricity decarbonization; Power sector; Renewable energy; Fuel switch; Combined heat and power; Electricity market modeling; Model comparison; Model-related uncertainty